2020
DOI: 10.1038/s41598-020-59573-4
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI Mapping of Human Meniscus Functionality and its Relation to Degeneration

Abstract: Meniscus pathology may promote early osteoarthritis. this study assessed human meniscus functionality (i.e. its response to loading) ex vivo based on quantitative T1, T1ρ, and T2 mapping as a function of histological degeneration and loading. Forty-five meniscus samples of variable degeneration were harvested from the lateral meniscus body region of 45 patients during total knee arthroplasties. Samples underwent serial mapping on a 3.0-T MRI scanner (Achieva, Philips) using a force-controlled and torque-induci… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Although overexercise can elevate the risk of OA, it is usually considered a genetically driven disease [1]. In recent years, the pathological variations of the cellular components, especially the pathogenic meniscus and vasculature in OA, have garnered increasing attention [2][3][4]. Although the vasculature in the joint was observed to be abnormal in patients with OA [1,5], its molecular mechanism is still difficult to understand, as research is impacted by a technique limitation in acquiring sufficient endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although overexercise can elevate the risk of OA, it is usually considered a genetically driven disease [1]. In recent years, the pathological variations of the cellular components, especially the pathogenic meniscus and vasculature in OA, have garnered increasing attention [2][3][4]. Although the vasculature in the joint was observed to be abnormal in patients with OA [1,5], its molecular mechanism is still difficult to understand, as research is impacted by a technique limitation in acquiring sufficient endothelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…In the alternative hypothesis, the extruded meniscus outside the joint J o u r n a l P r e -p r o o f margin is not compressed by the bones forming the joint which provides the opportunity for the meniscus to expand [7]. Recently published studies indicated that the delta-meniscus volume in vitro and in vivo could be initiated by load alteration on the meniscus [32,33]. The results in our study were consistent with this hypothesis, with baseline meniscus extrusion being positively associated with change in meniscus volume.…”
Section: Discussionmentioning
confidence: 99%
“…Segmentation outlines were checked by SN and validated against the corresponding WATSc images. These post-processing routines were implemented in MATLAB as before [21,22].…”
Section: Mri-quantitative Analysismentioning
confidence: 99%